Pilot Data on the Feasibility And Clinical Outcomes of a Nomegestrol Acetate Oral Contraceptive Pill in Women With Premenstrual Dysphoric Disorder - Robertson, Emily; Thew, Caroline; Thomas, Natalie; Karimi, Leila; Kulkarni, Jayashri (Frontiers in Endocrinology, 2021)
Background: Up to 80% of reproductive-aged women experience premenstrual symptoms. Premenstrual Dysphoric Disorder (PMDD) is a severe form, affecting 2-5% of women. Combined oral contraceptive pills (COCPs) are used in the treatment of PMDD. Clinical practice suggests that a newer COCP containing nomegestrol acetate (2.5mg) and 17-beta estradiol (1.5mg), may be a suitable treatment for mood symptoms in PMDD. Materials and Methods: This was a clinical follow-up feasibility study of women who had attended the Monash Alfred Psychiatry research centre, Women's Mental Health Clinic, with a diagnosis of PMDD. 67% of the sample also had concurrent cPTSD, 29% co-morbid anxiety, and 20% depression.They were recommended treatment with nomegestrol acetate/17-beta estradiol. Eligible women were contacted by telephone to answer a questionnaire to assess women's subjective response to nomegestrol acetate/17-beta estradiol, acceptability and the Depression, Anxiety and Stress Scale-21 (DASS-21) after being recommended nomegestrol acetate/17-beta estradiol. The paired-sample t-test was used to determine if there were any statistically significant differences in the DASS-21 scores over the study observation period (before and after taking nomegestrol acetate/17-beta estradiol). Results: 35 (74.5%) women reported a subjective positive mood response to nomegestrol acetate/17-beta estradiol, 31 (63.3%) adhered to the medication, and only 10 (20.4%) women reported side effects as the main reason for discontinuing nomegestrol acetate/17-beta estradiol. There were statistically significant reductions (p<0.05) in the overall DASS-21 scores from before women commenced nomegestrol acetate/17-beta estradiol and after commencement of treatment. Conclusions: This preliminary study supports the acceptability and effectiveness of nomegestrol acetate/17-beta estradiol as a treatment for mood symptoms in PMDD. Further research, particularly a randomised controlled trial, is required to elucidate the effect of nomegestrol acetate/17-beta estradiol treatment on mood in PMDD.